2022
DOI: 10.1108/jfra-06-2022-0234
|View full text |Cite
|
Sign up to set email alerts
|

Public perceptions of governance and tax evasion: insights from developed and developing economies

Abstract: Purpose This paper aims to explore how the role of the perception of good public governance reduces tax evasion (TE). Besides, this study investigates whether the nexus of public governance and TE differs between developed and developing economies. Design/methodology/approach Apart from the ordinary least squares (OLS) model, this study uses the linear mixed modeling technique. The World Governance Indicators and the multiple causes estimation (MIMIC) method are used to measure public governance. The shadow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…According to Feld and Tyran (2002), rational taxpayers exhibit greater tax morale and increased tax compliance when they believe that the tax code represents their views and the preferences of the majority. Nimer et al (2022b) have found a significant negative relationship between VA and tax evasion in developed countries.…”
Section: Governance Quality and Tax Evasionmentioning
confidence: 97%
See 4 more Smart Citations
“…According to Feld and Tyran (2002), rational taxpayers exhibit greater tax morale and increased tax compliance when they believe that the tax code represents their views and the preferences of the majority. Nimer et al (2022b) have found a significant negative relationship between VA and tax evasion in developed countries.…”
Section: Governance Quality and Tax Evasionmentioning
confidence: 97%
“…When taxpayers are uncertain about the future, they are more likely to hold cash and postpone their tax duties. Prior research has found a negative relationship between political stability and tax evasion (Nimer et al, 2022b).…”
Section: Governance Quality and Tax Evasionmentioning
confidence: 98%
See 3 more Smart Citations